IMPLICATURE ANALYSIS ON ONLINE LECTURE COURSES OF ENGLISH EDUCATION STUDY PROGRAM - Nadhea Intan Fitria; Agustinus Hary Setyawan (FKIP, Universitas Banten Jaya, 2023)
This research aims to reveal the types and implied meaning of implicature found in an online lecture courses of English education study program at one of the university in Yogyakarta. In this research using descriptive qualitative research methods by a theory from Grice (1975). The data findings consist of the three main implicatures consist of generalized conversational implicature with 14.3%, particularized conversational implicature with 8.6% and conventional implicature with 8.6%. Then, the four implicature functions are reach the intended meaning with 20%, deliver an entertainment as humor with 8.6%, boosting the power's of person's message with 14.3%, and specific information needs to be added with 25.6%. By adding up the total between main implicature and implicature functions, it turns out to be 100%. The three main implicature most widely used is generalized conversational implicature. As well as the most frequently used in the implicature function is, specific information needs to be added.